(untitled) (International Journal of Engineering and Computer Science, 2015)
In the era of information technology, Social sensing [1][3] is a latest useful technology for collecting the information which is directly associated with the human and other social resources. Most common example of social sensors are smart phones( mobile), in the smart phone , there exists many in-built sensors like GPS, Bluetooth, Wi-Fi and other location finding apps, temperature mapping sensors. The sensor are not used only in mobiles but also in automobiles vehicles like Bus, Car, Oven, Television, microwave etc. in smart kitchen to make smart home. The main concept is to make knowledge based society and intelligent system on the national and international level. Smart city is todays as well as future demand in the modern society for every country to arrange and run the social system in proper, efficient and effective manner. In this paper, the efforts have been made for various aspects of a smart city design and Implementation.